Pengaruh Kualitas Produk, Kualitas Layanan, Citra Perusahaan dan Nilai Pelanggan Terhadap Kepuasan Pelanggan Indihome - Muhammad Syahwi; Setyo Pantawis (ECONBANK: Journal of Economics and Banking, 2021)
Customer satisfaction is a feeling of pleasure or displeasure with a product or service from a company. This study aims to analyze the effect of product quality, service quality, corporate image and customer value on customer satisfaction. A total of 100 indihome customers in Semarang City were taken as samples by purposive sampling. The data analysis technique used in this research is multiple linear regression analysis. The results showed that product quality, company image and customer value had a positive and significant effect. While the service quality variable has no effect on customer satisfaction. The customer value variable has the most dominant influence on indihome customer satisfaction in the city of Semarang